2004
DOI: 10.1177/0891988703262539
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effects from UPBEAT: A Randomized Trial of Care Management for Behavioral Health Problems in Hospitalized Elderly Patients

Abstract: The purpose of this study was to examine the impact of the Unified Psychogeriatric Biopsychosocial Evaluation and Treatment (UPBEAT) Program, an interdisciplinary mental health care management program, on the behavioral health symptoms of elderly veterans. Participants, 60 years and older, included 2637 veterans recruited from medical/surgical units who screened positively for significant depressive or anxiety symptoms and/or at-risk alcohol drinking. Participants were randomized to UPBEAT or to usual care. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Lim, Lambert, and Gray (2003) also found that elderly under care management after hospital discharge had significantly better quality of life. Similar findings were observed in other studies (Allen & Meduna, 1999;Anderson-Loftin, 1995;Oslin et al, 2004).…”
Section: Introductionsupporting
confidence: 92%
“…Lim, Lambert, and Gray (2003) also found that elderly under care management after hospital discharge had significantly better quality of life. Similar findings were observed in other studies (Allen & Meduna, 1999;Anderson-Loftin, 1995;Oslin et al, 2004).…”
Section: Introductionsupporting
confidence: 92%
“…First, the use of a depression severity scale to identify and monitor patients with a potentially poor prognosis may be a more feasible and reliable method than the use of diagnostic criteria, both because it may be used by non-psychiatrists, and because a rating scale may be more responsive to change. Second, the demonstrated persistence of depression symptoms in this population should motivate efforts to develop effective interventions, in spite of disappointing outcomes of RCTs of interventions targeting depression in this population (Oslin et al, 2004;Cole et al, 2006). Third, better intervention results may be achieved by targeting the intervention to those at greatest risk of a severe course.…”
Section: Discussionmentioning
confidence: 97%
“…35 That intervention involved assessment by a multidisciplinary team and assignment of a case coordinator who engaged patients in treatment and follow-up. The rate of attrition through withdrawal and death was as high as our rate (60%).…”
Section: Discussionmentioning
confidence: 99%